Smart Youth For Diabetes Prevention: Transformation of Adolescents' Health Cadre Knowledge Through School-Based Educational Media at SMA Pasundan 3 Bandung City - Dian Yuniar Syanti Rahayu; Supriadi Supriadi; Susi Susanti; Sugiyanto Sugiyanto (Jurnal Kreativitas Pengabdian Kepada Masyarakat (PKM), 2026)
ABSTRACT The prevalence of Diabetes Mellitus (DM) among adolescents shows an increasing trend, yet adequate health literacy within school settings remains insufficient. This community service program aimed to improve the knowledge of Adolescent Health Cadres (KKR) regarding DM prevention through the Smart Youth for Diabetes Prevention initiative. The program applied a community empowerment approach incorporating health education, cadre training, dissemination of booklets and video media, and peer educator practice mentoring, involving 25 students from SMA Pasundan Bandung. Evaluation results demonstrated significant cognitive transformation, with all participants (100%) achieving the "Good" knowledge category and a mean score increase from 72.2 to 92.8. The program recommends institutionalizing activities within the School Health Unit (UKS) and strengthening cross-sector collaboration among schools, primary health centers, and academics to sustain early detection of Noncommunicable disease risk factors among adolescents. Keywords: Adolescent Health Cadre, Diabetes Mellitus, Educational Media, Health Literacy, Peer Educator.